Pouvoir de bactéries probiotiques dans la lutte contre l’allergie alimentaire - Elomari, Zineb (My University, 2020)
Although the prevalence of food allergies is rising, the standard of care medical for these types of allergies is suboptimal. Probiotics have been reported to regulate the allergic immune response, but the underlying mechanisms are not fully understood. In this study, we detail in a new research which aims to evaluate the effect of a mixture of probiotics on food allergy in an ovalbumin (OVA)-induced murine model according to the work of Ma et al. (2019). The results found in this recent study showed that the treatment with the probiotics attenuated OVA-induced allergic symptoms in mice. Flow cytometry analysis showed that oral administration of probiotics induced the dendritic cells, which promoted differentiation of regulatory T cells. 16S rRNA analysis revealed that the probiotics modulated the composition of microbiota, especially by increasing the proportion of the Deferribacteres and Verrucomicrobia phyla and the Mucispirillum and Clostridium XlVa genera, which in turn regulated the immune system. These findings provide a clear molecular insight into the application of a mixture of probiotics to alleviate food allergies and even to protect gut immune homeostasis.
Keywords: Gut microbiota; Food allergy; Oral tolerance; Probiotics; Dendrit ic cells